2010
DOI: 10.1093/aob/mcq163
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of thiourea-modulated salinity stress-responsive transcripts in seeds of Brassica juncea: identification of signalling and effector components of stress tolerance

Abstract: The TU treatment co-ordinately regulates different signalling and effector mechanisms at an early stage to alleviate stress even under a high degree of salinity. This also indicates the potential of TU to be used as an effective bioregulator to impart salinity tolerance under field conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…This shows the antioxidant activity of these exogenously applied organic compounds in scavenging ROS. These findings of the present study are analogous to some previous studies in which it was reported that foliar applications of mannitol and thiourea are effective in reducing the adverse effects of oxidative stress on biological membranes by acting as a scavenger of ROS (Mitoi et al 2009;Srivastava et al 2010). …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This shows the antioxidant activity of these exogenously applied organic compounds in scavenging ROS. These findings of the present study are analogous to some previous studies in which it was reported that foliar applications of mannitol and thiourea are effective in reducing the adverse effects of oxidative stress on biological membranes by acting as a scavenger of ROS (Mitoi et al 2009;Srivastava et al 2010). …”
Section: Discussionsupporting
confidence: 92%
“…Of them, thiourea plays a key role in oxidative stress response. Recently, Srivastava et al (2010) have reported that thiourea treatment can alleviate the adverse effects of salt stress on Brassica juncea seeds by coordinately bioregulating different signaling and effecter mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of the gene-specific primer sets were GCCGGAG-TATCGGTCCTTTTTCG-F and AGCCGCTCTGAT-CACTTCAATCTG-R for phenyl-alanine ammonia lyase (pal) and ACCTGCAGGCATCTTGGCTATTGG-F and ACTGCCGCTTCTTTGCCTAGCTT-R for chalcone synthase (chs). The RNA isolation and quantitative real-time PCR were performed as per the method described previously (Srivastava et al 2010b). …”
Section: Estimation Of Proline Contentmentioning
confidence: 99%
“…In this situation, use of growth substances provides a short-term solution to overcome environmental stresses. In recent times, attention has been diverted to the improvement of crops for stress tolerance by enhanced biosynthesis or exogenous application of growth substances (Naidu and Williams, 2004;Quan et al, 2004) Srivastava et al (2010) while working with Brassica juncea have shown that exogenously applied thiourea can effectively alleviate the inhibitory effects of saline stress on B. juncea seeds by regulating signaling mechanisms. However, the effectiveness of thiourea and related growth regulators has been reported to depend on plant species, environmental conditions, and concentration of soil salt solution.…”
Section: Introductionmentioning
confidence: 99%